THE PROFILE OF THE AGED PARTICIPANT OF STREET RACE IN COMPARISON TO THE SEDENTARY ONES IN GOIÂNIA CITY (Fiep Bulletin - online, 2011)
This research had as objective to achieve a pre-investigation of the profile of the aged participant of street race and to compare some data with the sedentary people in Goiânia city. It was used a research with an application of a questionnaire and statistical treatment of the average, shunting line standard, test-t and distributions of frequency for comparison and presentation of the results. 50 male practitioners of street race had been evaluated with the average of age of 64,96±5,36, 50 sedentary ones with the average of 67,68±6,54. In relation to the body mass index, the average of the runners was 23,39±3,26 and of the sedentary ones was 25,21±3,20 p= 0.1%. The research showed that 70% of men participate of the race on their ones, without orientation of a specialized professional. In relation to the control of systolic blood pressure and diastolic blood pressure, the sedentary ones consume a great number of specific medicines. 64% who had habit to smoke, quit smoking after initiating the practical of the race. It concludes that the practical one of the race is significant in the contribution of the quality of life of the old people.
Keywords: Aged; Sedentary; Street Race